Top

Foil Calculator
Top
Foil calculator or Foil method Calculator helps to find the simplified product of the two terms. It acts a tool that find the product calculator using the Foil rule. Foiling Calculator is a tool that makes the calculation fun full as it gives you the answer instantly once you enter the expression.

The Foil is the acronym which shows the method to perform multiplication.
The word FOIL stands for:
F = First
O = outer
I = Inner
L = Last.

Below figure helps you to understand the foil method:

Below is given two default binomials, click "Evaluate the integral". Using Foil method, it calculates the product of the binomials.

## Steps for Foil Calculator

Step 1 :

Multiply first term of the first bracket to the first term of the other bracket

Step 2 :

Then multiply the first term of the first bracket to the last term of the second bracket.

Step 3 :

Now come to the second term of first bracket, multiply second term with first term of second bracket.

Step 4 :

Finally multiply last term of first bracket with the last term of the second bracket.

Step 5 :

## Problems on Foil Calculator

1. ### (2x + 3)(3x + 4)

Step 1 :

Multiply first term of the first expression with first term of second expression

2x $\times$ 3x = 6X2

Step 2 :

Then Multiply first term of first expression with second term of second expression

2x $\times$ 4 = 8x

Step 3 :

Now multiply the second term of first expression with second term of second expression
3 $\times$ 3x = 9x

Step 4 :

Lastly multiply second term of first expression with second term of second expression
3 $\times$ 4 = 12

Step 5 :

6x2 + 8x + 9x + 12.

6x2 + 17x + 12

2. ### (4x + 3)( 5x + 3)

Step 1 :

Multiply first term of the first expression with first term of second expression

4x $\times$ 5x = 20 x2

Step 2 :

Then Multiply first term of first expression with second term of second expression

4x $\times$ 3 = 12 x

Step 3 :

Now multiply the second term of first expression with second term of second expression

3 $\times$ 5x = 15x

Step 4 :

Lastly multiply second term of first expression with second term of second expression

3 $\times$ 3 = 9

Step 5 :

20x2 + 12x + 15x + 9.

20x2 + 27x +9

3. ### A university student designed a rectangular picture frame. The picture measures 17 cm by 11 cm. The total area of the picture frame is 315 cm$^2$. Find the width of the frame.

Step 1 :

Let x be the width of the frame.

Length and Width of the picture frame are 17 + 2x and 11 + 2x respectively.

Step 2 :

Since area of picture frame = 315 cm$^2$

=> (17 + 2x)(11 + 2x) = 315  (Because area of rectangle = Length * Width)

Step 3 :

17(11 + 2x) + 2x(11 + 2x) = 315 (Foil method)

187 + 34x + 22x + 4x$^2$ = 315

4x$^2$ + 56x + 187 = 315

4x$^2$ + 56x - 128 = 0

4(x + 16)(x - 2) = 0  (Factorized)

x + 16 = 0 and x - 2 = 0

x =  -16 and x = 2

Step 4 :

Length can't be negative. So our value is x = 2.

Step 5 :

Width of the frame is 2 cm.